Descriptive Study of Academic Procrastination in Students Doing Thesis at Padang State University - Meldya Wati; Mario Pratama (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
This research is a descriptive study that discusses academic procrastination among students working on their theses at Padang State University. Academic procrastination is irrational behavior carried out by students intentionally which in the end can affect the performance of a given assignment. This research uses quantitative research with a descriptive approach. In this research, the number of subjects used was 265 students who were working on their thesis at Padang State University, with details of 168 men and 97 women. Subjects were selected using cluster sampling techniques. The data collection technique uses a Likert scale. The research results show that there is a difference between the empirical mean and the hypothetical mean where the empirical mean shows a score of 88.27 while the hypothetical mean shows a score of 75. This means that the empirical mean score is greater than the hypothetical mean. This data shows that the academic procrastination of these students tends to be high.